(untitled) (Research, Society and Development, 2025)
This integrative literature review examines the importance of radiography within Brazil’s Unified Health System (SUS), synthesizing evidence from studies published between 2021 and 2025 regarding its clinical relevance, epidemiological impact, structural challenges, and management implications. Analysis of the seven selected articles demonstrates that radiography remains the most frequently used imaging modality in public healthcare, accounting for the majority of diagnostic output and serving as an essential tool across all levels of care. Findings show that the COVID-19 pandemic significantly reduced outpatient imaging volumes while simultaneously reinforcing the centrality of chest X-rays for respiratory triage and monitoring. Marked regional inequalities in equipment distribution and radiology resources were identified, affecting access to examinations and contributing to disparities in clinical outcomes. Radiography also plays a critical role in priority health areas such as tuberculosis, oral health, trauma, and chronic diseases, reaffirming its indispensability within the current diagnostic environment. Cost analyses and digital transformation studies highlight opportunities to optimize workflows through systems such as Vendor Neutral Archive (VNA), particularly due to the high national demand for radiographic services. Overall, radiography is shown to be strategic for ensuring access, equity, and efficiency within SUS, underscoring the need for continuous investment in infrastructure, digital integration, professional training, and evidence-based management policies.